1992
DOI: 10.1152/ajpendo.1992.262.2.e155
|View full text |Cite
|
Sign up to set email alerts
|

Glycylglutamine: metabolism and effects on organ balances of amino acids in postabsorptive and starved subjects

Abstract: The present study was designed to investigate the metabolism of glycylglutamine and its effects on organ balances of amino acids during intravenous infusion of this dipeptide (100 mumol.h-1.kg-1) in postabsorptive and briefly starved (84-86 h) human subjects. Arterial concentrations of glycylglutamine were not significantly different in postabsorptive (265 +/- 18 microM) and starved (241 +/- 13 microM) subjects. Among the organs examined, kidney predominated in clearance of glycylglutamine from plasma. Moreove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 1 publication
2
6
0
1
Order By: Relevance
“…Our net renal balance data for alanine, glycerol, and glutamine are in general agreement with previous reports (9,12,16,31,49,50). Our data for renal lactate net uptake (ϳ170 mol/min) are essentially identical to those reported by Cersosimo and colleagues (9, 12) (ϳ170 mol/min).…”
Section: Discussionsupporting
confidence: 92%
“…Our net renal balance data for alanine, glycerol, and glutamine are in general agreement with previous reports (9,12,16,31,49,50). Our data for renal lactate net uptake (ϳ170 mol/min) are essentially identical to those reported by Cersosimo and colleagues (9, 12) (ϳ170 mol/min).…”
Section: Discussionsupporting
confidence: 92%
“…The participation of individual organs in the disappearance of glutamine dipeptides has also been investigated by Abumrad et a126 in dogs and by Lochs et al2l,28 in humans. In humans, as in dogs, the kidneys, muscle, and splanchnic organs participated in the removal of dipeptides (Fig 8).…”
Section: Fate Of Intravenously Administered Dipeptidesmentioning
confidence: 95%
“…Whether these cis elements play a role in controlling gene expression in the kidney in response to cellular availability of free amino acids and dipeptides needs to be determined. However, studies in humans suggest that starvation reduces renal peptide transport activity, as demonstrated by a reduction in removal of the intravenously infused dipeptide Gly-Gln by the kidney (4,42). In the yeast Saccharomyces cerevisiae, gene expression of Ptr-2, the yeast peptide transporter (50), is upregulated at the expression level by selected dipeptides that activate an ubiquitin-dependent proteolytic pathway (69).…”
Section: Regulation Of Expression Level and Transport Activity Of Pepmentioning
confidence: 99%